V-BAG: A virtual bandwidth aggregation scheme for Internet of Things data. (April 2017) - Gwak, Yongsu; Kim, Young Yong; Kim, Ronny Yongho
In order to meet the two crucial requirements of Internet of Things (support of a large number of Internet of Things devices and low power consumption), this article proposes a novel and efficient virtual bandwidth aggregation scheme for Internet of Things data. Since many Internet of Things applications require reliable Internet of Things data transmission, a Transmission Control Protocol is chosen as a transport protocol in this article. The proposed scheme consists of three salient functions: packet scheduler, estimator, and ACK buffer. The packet scheduler provides an efficient heterogeneous link selection using the proposed scheduling algorithm. The estimator provides an accurate delay and bandwidth estimation of heterogeneous wireless links using network layer information. Finally, the ACK buffer substantially boosts the performance of the scheduler and estimator with a simple ACK buffering scheme. Our extensive analysis using a numerical method and simulation corroborates the outstanding performance of the proposed scheme. Because of the salient functions of the proposed scheme, it can provide maximum capacity for future Internet of Things data transmission.